Kinerja Keuangan Bank Sebelum dan Sesudah Konversi ke Bank Syariah (Studi Pada Bank NTB Syariah) - Fahdiansyah, Restu (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2021)
This study aims to determine how the impact of the conversion process of BankNTB Syariah which was previously a conventional bank on the financialperformance of Bank NTB Syariah, by comparing the financial performance beforeand after the conversion process is carried out. The approach used in this study isa descriptive qualitative method with financial statement analysis techniques toanswer research questions, by comparing the liquidity ratio (Loan to Deposit Ratio)and the profitability ratio (Return on Assets and Return on Equity) before and afterconversion. The data used in this study is secondary data derived from the annualfinancial statements of Bank NTB Syariah before and after the conversion process.This study shows that the comparison of the financial performance of PT. Bank NTBbefore and after conversion to Bank NTB Syariah several main financial ratios havereached the target that has been set.